2016
DOI: 10.1038/srep32875
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and clinical utility of a new noninvasive index for hepatic steatosis in patients with hepatitis B virus infection

Abstract: The aim of the present study was to construct a cost-effective noninvasive diagnostic index for prediction of hepatic steatosis in patients with hepatitis B virus(HBV) infection. From January 2011 to January 2015, a total of 364 consecutive subjects who underwent liver biopsies were enrolled. The Receiver-operating characteristic(ROC) curves and Obuchowski measure were constructed to evaluate the diagnostic accuracy of the new index. The AUROCs of steatosis index of patients with HBV infection (SIHBV) in predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…Accordingly, it is plausible that the LAP, which is a combination of WC and fasting TG, is significantly associated with NAFLD. However, few studies have so far investigated the association between LAP and NAFLD, and the existing studies have been conducted primarily in subjects with chronic diseases, such as HIV infection [ 45 ], hepatitis B virus infection [ 46 ], and polycystic ovary syndrome [ 47 ], with inconsistent results. Whether LAP is an effective maker for NAFLD that could be widely applied in general Chinese population remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is plausible that the LAP, which is a combination of WC and fasting TG, is significantly associated with NAFLD. However, few studies have so far investigated the association between LAP and NAFLD, and the existing studies have been conducted primarily in subjects with chronic diseases, such as HIV infection [ 45 ], hepatitis B virus infection [ 46 ], and polycystic ovary syndrome [ 47 ], with inconsistent results. Whether LAP is an effective maker for NAFLD that could be widely applied in general Chinese population remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic steatosis index (HSI), which is based on levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and body-mass index (BMI), is a useful index to diagnose NAFLD that has been validated in various studies [ 35 , 36 , 37 , 38 , 39 , 40 ]. HSI was reported to have an area under the receiver operating characteristic (AUROC) of 0.81 for the diagnosis of NAFLD [ 35 ], which, although a slightly lower AUROC than that of the Framingham Steatosis Index, was of diagnostic value [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported an AUROC of 0.83 for HSI and the tool was deemed to be convenient [ 37 ]. Moreover, HSI is cost effective and can be performed before computed tomography (CT) and magnetic resonance imaging (MRI) based diagnoses [ 38 ]. In a large-scale cohort study, HSI was found to be an effective indicator for predicting NAFLD in comparison to results using ultrasound [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these models, however, included parameters not always routinely measured in clinical practice. For example, models have included serum concentrations of insulin (24), uric acid (25), hemoglobin A1C (19), and haptoglobin (26), as well as waist circumference (15,27), which are parameters that may not be easily retrieved from patient databases. This may limit the use of these models in retrospective analyses.…”
Section: Discussionmentioning
confidence: 99%